Temperature dependence laser-assist scattering and its impact on efficiency of PEMFC - Saddam Husain Dhobi; Kishori Yadav; Suresh Prasad Gupta; Jeevan Jyoti Nakarmi; Ajay Kumar Jha (PLoS ONE, 2026)
Proton Exchange Membrane Fuel Cells (PEMFCs) is one of the best promising clean technologies in future. Numerous research activities are going on regarding to stability and thermal management of PEMFC. This reserch aim to study the scattering dynamic inside PEMFC in self-generated heat, laser field and scattering particles. To fulfil this objective first, authors developed theoretical model and then verified some parameters of theoretical model with experimental methods. For theoretical model authors formulated transition matrix using thermal Volkov wave function and thermal potential of hydrogen to study scattering dynamic. For experimental method, authors developed a PEMFC prototypes and applied diffident condition (heat and laser) to observed the data for verification of theoretical model. The developed differential cross section (DCS) model shows that with increasing temperature DCS increase theoretically and experimentally found that increasing in temperature decreasing in voltage. So, the DCS increasing with decreasing in voltage which is verified both theoretically and experimentally. In addition, we also observed that DCS effect by different parameters of PEMFC like charge transfer, charge density, efficiency, voltage, activation potential etc. and scattering parameters like momentum, scattering angle, incidence energy, distance separation etc. This finding help both academic field and non-academic field like scanning tunneling microscopy, laser-induced fluorescence, quantum computing and nanophotonic sensors perform. The finding finds that the supply temperature negatively influences PEMFC performance, which is attributed to higher particles’ resistance and entropy, hence indicating how stringent is the requirement for an accurate thermal management for enhancing fuel cell efficiency.